(untitled) (UNIZIK Journal of Educational Management and Policy, 2024)
Principals’ effective management of school plant encourages personnel in schools to be better and committed to effective service delivery. The application of good management of school plant invariably improves productivity which will in turn influence the achievement of educational objectives. The main purpose of this study was to examine principals’ management of school plant as correlate of teachers’ job commitment in public secondary schools in Anambra State. Two research questions guided the study and two null hypotheses were tested at 0.05 level of significance. The study adopted correlational research design. The population of the study comprised 5,133 teachers in 266 public secondary schools in the six Education Zones in Anambra State. The sample of 513 teachers was used for the study. Multi stage sampling procedure was used for the study. The instruments for data collection were researchers-structured questionnaire titled: Principals’ Management of School Plant Questionnaire (PMSPQ) and Teachers’ Job Commitment Questionnaire (TJCQ). The instruments were validated by three experts. The reliability of the instruments were determined using Cronbach Alpha Coefficient method to determine the internal consistency. The average coefficient for PMSPQ is 0.81 and 0.80 for TJCQ. The researchers adopted on-the-spot delivery method with the help of four trained research assistants to collect the data. Pearson Product Moment Correlation Coefficient was used for the study. The findings of the study showed that principals’ management of school building and principals’ management of school premises positively and significantly correlate with teachers’ job commitment in public secondary schools in Anambra State. The study recommended among others that faults detected by school principals as regards the functionality of any school building should be reported to appropriate authorities to be rectified to avoid total disruption of educational activities.